Amorphous RuO2 Catalyst for Medium Size Carboxylic Acid to Alkane Dimer Selective Kolbe Electrolysis in an Aqueous Environment - Wang, Chong; Liu, Kaixin; Jin, Yangxin; Huang, Shuquan; Chun‐Ho Lam, Jason (ChemSusChem, 2023)
The catalytic transformation of biomass‐derived volatile carboxylic acids in an aqueous environment is crucial to developing a sustainable biorefinery. To date, Kolbe electrolysis remains arguably the most effective means to convert energy‐diluted aliphatic carboxylic acids (carboxylate) to alkane for biofuel production. This paper reports the use of a structurally disordered amorphous RuO2 (a‐RuO2) that is synthesized facilely in a hydrothermal method. The a‐RuO2 is highly effective towards electrocatalytic oxidative decarboxylation of hexanoic acid and is able to produce the Kolbe product, decane, with a yield 5.4 times greater than that of commercial RuO2. A systematic study of the reaction temperature, current intensity, and electrolyte concentration reveals the enhanced Kolbe product yield is attributable to the more efficient oxidation of the carboxylate anions for the alkane dimer formation. Our work showcases a new design idea for establishing an efficient electrocatalysts for decarboxylation coupling reaction, providing a new electrocatalyst candidate for Kolbe electrolysis. An amorphous RuO2 was effectively fabricated via a facile hydrothermal method. The amorphous structure and introduction of oxygen vacancies endow the sample better stability and electron transfer efficiency, which remarkably enhances the activity of electrocatalytic Kolbe oxidation of hexanoic acid.